Mendelian randomization study of IGF-1, childhood obesity and obesity-related asthma: Relationship between IGF-1 and childhood obesity-related asthma - Zhu, Tianyi; Liu, Hao; Ling, Lan; Wang, Yang; Jin, Chao; Qi, Jirong; Zhou, Chen (Cellular and Molecular Biology, 2023)
Insulin-like growth factor 1 (IGF-1) has been reported to potentially link with childhood obesity and obesity-related asthma, although a causal effect has not been illustrated. This study aimed to assess their association via multi-variable Mendelian randomization (MR) analysis with two-sample summary-level data on genetic variants as instrumental variables, thus estimating a causal effect. Genetic variants associated with serum IGF‐1 at genome‐wide significance (GWS) in the UK Biobank study involving 363,228 individuals of European descent were introduced as instrumental variables. Summary-level data on childhood obesity and obesity-related asthma were obtained from genome-wide association studies (GWAS). Here, MR-Egger, inverse-variance weighted (IVW), simple median, weighted median and penalized weighted median methods were used in the MR study. Results showed that there were strong causal associations of IGF-1 with childhood obesity (OR, 1.27; 95% CI 1.01-1.60; P<0.05) and obesity-related asthma (OR, 1.22; 95% CI 1.07-1.38; P<0.005). In conclusion, A causal association between high IGF-1 levels and high risks of childhood obesity and obesity-related asthma is estimated, which requires further validation in large-scale trials.